Conflict management in dentistry - I. A. Belenova; A. V. Mitronin; O. A. Azarova; A. V. Podoprigora; O. A. Kudryavtsev (Эндодонтия Today)
The problem of convicts arising between a doctor and a patient in a dental clinic is presented. The characteristic of con^ictogenic personalities and con^ictogenic situations, the occurrence of which is possible at a dental appointment, is given. The ways and methods of creating an optimal relationship between a dentist and a patient are presented, which allows you to conducttreatmentwith maximum ef^ciency and mutual bene^t. Dentists, starting their independent professional activities, should correctly use psychological skills at outpatient appointments: the ability to speak, hear, persuade, establish positive interpersonal contacts with different psychological types of patients, recognize emerging convicts at the initial stage, not get involved in the convict itself, be able to manage the convict and extinguish it using psychological techniques and techniques. Fully meet the expectations of the patient who has applied for help in a medical institution.